2008
DOI: 10.1177/0891242407309822
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating the Creative Class: And What About Nanaimo?

Abstract: Despite widespread adoption of creative class economic development strategies, one of its basic tenets—the connection between community tolerance (running through talented individuals and high-tech employment) and economic health and growth—has not been sufficiently tested. This analysis of 40 midsized Canadian urban areas finds a connection between diversity and gay and creative populations and economic health. Neither high-tech employment nor economic growth, however, was found to be linked to the other meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 27 publications
2
60
0
Order By: Relevance
“…Factors related to the institutional support are: labour market mobility (Lorenz et al 2010), education system (Lorenz, Lundvall 2010;Spencer 2011), innovations in residential areas (Walcott 2002;Sands, Reese 2008), economic diversity in residential areas (Desrochers, Leppälä 2010), university system (Florida 2005), cluster system (Schoales 2006;Jucevičius 2009), public investment in education and research, and tax incentives for scientists and their researches (Schoales 2006).…”
Section: Evaluation Of Factors Affecting Creativity 21 Theoretical mentioning
confidence: 99%
See 1 more Smart Citation
“…Factors related to the institutional support are: labour market mobility (Lorenz et al 2010), education system (Lorenz, Lundvall 2010;Spencer 2011), innovations in residential areas (Walcott 2002;Sands, Reese 2008), economic diversity in residential areas (Desrochers, Leppälä 2010), university system (Florida 2005), cluster system (Schoales 2006;Jucevičius 2009), public investment in education and research, and tax incentives for scientists and their researches (Schoales 2006).…”
Section: Evaluation Of Factors Affecting Creativity 21 Theoretical mentioning
confidence: 99%
“…Factors related to the sets of values and norms are: public culture (Glaveanu 2010), tolerance (Sands, Reese 2008), local environment's tolerance, diversity and size of the residential area (Spencer 2011), revolutionary (major) changes (Livingstone et al 2002), competition, and social mobility (Pruskus 2004;Simon 2005;Klimašauskienė 2007). Creativity is considered as a complicated and complex social phenomenon, as it is influenced by many interrelated factors acting in opposite directions.…”
Section: Evaluation Of Factors Affecting Creativity 21 Theoretical mentioning
confidence: 99%
“…Other applications of the creative class approach to Canada have concluded that the arts effect is really a product of large cities having critical mass rather than to causal interactions among the factors alleged to promote creativity (Lewis & Donald, 2010). A longitudinal study of 40 smaller Canadian cities has found that the creative class rubric is a poor predictor of local economic success (Sands & Reese, 2008).…”
Section: Finding Space For the Creative Classmentioning
confidence: 99%
“…Richard Florida (2002) suggests that factors such as tolerance and the presence of talented individuals (regardless of occupation) are essential to economic prosperity. Although Florida's causal linkages have not been empirically verified (see Madden 2001 andReese 2008), there is nevertheless an intuitive appeal to economic development strategies that emphasize tolerance of others and culture. In any case, including such factors may result in improved understanding of the potential for achieving local economic prosperity.…”
Section: Policy Issuesmentioning
confidence: 99%